Ruptured Iliac Arteriovenous Fistula Presenting With Thigh Pain and Swelling: Case Report - Morton, Claire; Endicott, Kendal M.; Penikis, Annalise; Toursavadkohi, Shahab; Hall, Michael R. (Frontiers in Surgery, 2022)
Patients with abdominal arteriovenous fistulas are most commonly identified by a classic presentation of pulsatile abdominal mass with bruit, high-output heart failure and regional venous hypertension. In the following case, we present the treatment of a patient who arrived with acute renal failure due to an arteriovenous fistula and who was successfully treated with endovascular repair.